Defending Williamson's Explanatory Challenge to Contingentism (Aporia, 2025)
This paper focuses on a particular challenge Timothy Williamson raised to contingentism in Chapter 6 of his book Modal Logic as Metaphysics and various responses towards this challenge. Section 2 reconstructs Williamson’s challenge; Section 3 explains two “trivialization" worries about this challenge and respond to them on Williamson’s behalf; Section 4 develops a possible substantive “anti-haecceitist" response to Williamson’s challenge and argue against this response. I argue that Williamson’s challenge is successful and contingentists have considerable dialectical disadvantages in trying to overcome the challenge.